The effects of lymphocele formation after living donor kidney transplantation on mid-term allograft function - Christian Kuhn; Bernd Jänigen; Laura Matuschik; Max J. Rieger; Daniel Sidler; Stefan Zschiedrich (BMC Nephrology)
Abstract Background Despite advances in kidney transplant surgery and immunosuppression, lymphoceles remain a frequent complication in the early postoperative period following kidney transplantation, often requiring reintervention. While long-term outcomes such as patient and allograft survival are well studied, the impact of lymphocele formation on mid-term allograft function remains unclear. Methods This multicentric study included 711 recipients of living donor kidney transplants to investigate the impact of lymphocele formation on mid-term graft function. Outcomes assessed included estimated glomerular filtration rate (eGFR) at 12 months, eGFR slope, and both patient and allograft survival. Results Lymphoceles were detected in 17.4% of the recipients, with a median volume of 129 ml, and 71.8% of these patients required intervention. Patients without lymphocele formation had a significantly higher median eGFR at 12 months (52.1 ml/min/1.73 m²) compared to those with lymphoceles (48.7 ml/min/1.73 m²). Additionally, patients with lymphocele formation demonstrated a steeper median eGFR slope (-2.3 ml/min/1.73 m²/year) than those without (-0.3 ml/min/1.73 m²/year). No significant difference was observed in the composite outcome of allograft survival and patient death between the two groups. Conclusion Lymphocele formation after living donor kidney transplantation is associated with a steeper decline in graft function. They may reflect a disturbed microvasculature and warrant closer control of cardiovascular risk factors and allograft monitoring of affected patients. Clinical trial details Not applicable, the study is not a clinical trial.